ACCELERATION OF LEARNING MANAGEMENT SYSTEM APPLICATION DEVELOPMENT IN THE EDUCATION SECTOR USING THE LOW CODE CONCEPT ON MICROGEN - Ega Wachid Radiegtya; Daniel Hasiholan Tinambunan; Rido Dwi Kurniawan; Richardus Eko Indrajit (Informatika, Universitas Jenderal Soedirman, 2023)
The background of this research is to speed up application development which tends to take a long time. To respond this, researchers apply the concept of